WARM, HEARTS, AND JOURNEY: CREATING MOMENTS AT WIJAYA KUSUMA - Hally Hanafiah (Lentera Ilmu Madani, 2026)
Aging is a natural process often accompanied by various physical and psychosocial challenges. To enhance the quality of life for the elderly, the community service event Warm, Hearts, and Journey was held at Wijaya Kusuma Nursing Home, Jakasampurna District, West Bekasi, on Sunday, July 20, 2025. This program aimed to provide emotional support and improve both mental and physical well-being through engaging and educational activities. The implementation used a participatory approach with warm interpersonal communication, including door-to-door interactions within the nursing home to ensure every resident felt cared for and valued. A multidisciplinary collaboration among students from various study programs enriched the event, creating a comfortable and empathetic atmosphere. The outcomes demonstrated increased enthusiasm and a stronger sense of togetherness among the elderly, while also highlighting the importance of social support in fostering meaningful aging experiences.